(untitled) (Stavební obzor - Civil Engineering Journal, 2022)
The main objective of this study of research is to initiate and develop a comparative study of fresh and hardened properties of concretes made from recycled sand from three types of waste: marble waste, tiling waste and cinder block waste. And this, in the intention of contributing to the world effort relating to the preserve of natural aggregate resources and limit landfill to the ultimate waste thresholds. To do this, in the composition of a current concrete with a water / cement ratio equal to 0.55, an equivalent volume of sand from the three wastes respectively replaced a volume of 15% of the ordinary sand. The properties in the fresh state: workability, air content and density and in the hardened state: compressive strength, Flexural tensile strength, compressive strength determined with non-destructive tests, water absorption by immersion, absorption by capillarity and chloride penetration of the various concretes produced are analyzed, and compared to those of the control concrete. The results obtained show that the concretes containing the waste sands have acceptable characteristics. However, tiling waste sand performs better than the other two recycled sands.